SINONIMITAS DALAM AL-QUR’AN (Makna Lafadz ‘Alima dan ‘Arofa Perspektif al-Zamakhsyari) - M. AZHARI, AZHARI (UIN Mataram, 2025)
This study examines the meaning of 'alima and 'arofa contained in the book of tafsir al-kasysysaf by al-Zamakhsyari, this study aims to provide new knowledge related to the meaning contained in the verses of 'alima and 'arofa. With regard to the meaning of 'alima and 'arofa which means knowing, is a trait that requires an object. So to know and understand it, linguistic analysis is needed. As an approach, the author uses thematic figures, namely, al-Zamakhsyari in the book of tafsir al-kasysysaf. In this research method using qualitative methods with the type of library research. Library research is a study in which all data are in the form of written materials such as books, journals, manuscripts and previous scientific research, which discusses lafadz 'alima and 'arofa in the book of tafsir al-kasysysaf by al-Zamakhsyari with descriptive analysis techniques. The results of this study indicate that the interpretation of al-Zamakhsyari in explaining the lafadz 'alima and 'arofa has similarities and differences. The similarities of the two are both